Portrait global de l’exposition aux contraintes psychosociales au travail des paramédics québécois - Sandrine Hegg-Deloye; Patrice Brassard; Jérôme Prairie; Dominique Larouche; Nathalie Jauvin; Angelo Tremblay; Philippe Corbeil (Perspectives Interdisciplinaires sur le Travail et la Santé)
Psychosocial constraints at work are a major concern, since they can have a pathogenic effect on the mental and physical health of workers. The purpose of this study was to provide an overview of these constraints in paramedics in Quebec. A cross-sectional study was conducted during the fall of 2010 and winter of 2011. In it, 295 paramedics responded to questionnaires related to two psychosocial risk models : the job demand-control-support model defined by Karasek and Theorell, and the effort/reward imbalance model defined by Siegrist. ANOVA with two between factors (gender and experience) was performed on all the measures obtained with the two models. Men were more exposed to lower social support, iso-strain, and job-strain than were women. Social support (from colleagues and superiors) decreased with years in employment, while remuneration was estimated highest in mid-career. Decision latitude and recognition represented favourable dimensions. The most critical dimensions were the lack of social support from colleagues and superiors, as well as extrinsic excessive efforts. The overall picture that emerged showed that three-quarters of the responding paramedics would seem to be exposed to a high risk of physical and mental health problems at work.